Comparative analysis of current health expenditure and mortality from COVID-19 by countries - Spichak, Irina V.; Zhirova, Irina V.; Podgaina, Maryna V.; Korzh, Yulia V.; Ivashchenkova, Alina O. (AVFT – Archivos Venezolanos de Farmacología y Terapéutica, 2021)
The research aimed to conduct a comparative assessment of mortality rates from COVID-19 and health expenditure in countries, where the COVID-19 had been found, in order to establish the correlation between these two indicators. Materials and methods. Data about current health expenditure per capita have been taken from the Data World Bank from the World Health Organization Global Health Expenditure Database. Worldwide mortality data of coronavirus have been used from Johns Hopkins University and medicine Coronavirus resource center where actual data of incidence and fatal cases are presented. Results. The results of the analysis have shown: among countries with a low level of health expenditures per capita the smallest share has corresponded to the countries with a high COVID-19 fatality rate – less than 20% (22 countries). Assessment of the volume of expenditures of these 22 countries indicates: 2 of them (9%) have had health expenditures per capita higher 2000 (Italy and Spain), 4 of them (18%) – from 1000 to 2000, and 4 countries have had health expenditures per capita less 200 . Conclusions. The results of our comparative study of health expenditures to COVID-19 case-fatality convincingly show that the absence of a direct correlation between the volume of health expenditure of the country and the COVID-19 fatality index